Clinical Significance and Potential Mechanisms of ATP Binding Cassette Subfamily C Genes in Hepatocellular Carcinoma - Zhou, Xin; Huang, Jia-mi; Li, Tian-man; Liu, Jun-qi; Wei, Zhong-liu; Lan, Chen-lu; Zhu, Guang-zhi; Liao, Xi-wen; Ye, Xin-ping; Peng, Tao (Frontiers in Genetics, 2022)
The purpose of this investigation was to assess diagnostic and prognostic significance of ATP binding cassette subfamily C (ABCC) genes in hepatocellular carcinoma (HCC). Student t-test was used to compare the expression level of ABCCs between HCC and paraneoplastic tissues. Receiver operating characteristic curve (ROC) analysis was applied for diagnostic efficiency assessment. Kaplan Meier method and Cox proportional hazards model were respectively applied for survival analysis. Genes with prognostic significance were subsequently used to construct prognostic models. From the perspective of genome-wide enrichment analysis, the mechanisms of prognosis-related ABCC genes were attempted to be elaborated by gene set enrichment analysis (GSEA). It was observed in TCGA database that ABCC1, ABCC4, ABCC5 and ABCC10 were significantly up-regulated in tumor tissues, while ABCC6 and ABCC7 were down-regulated in HCC tissues. ROC analysis revealed that ABCC7 might be a potential diagnostic biomarker in HCC. ABCC1, ABCC4, ABCC5 and ABCC6 were significantly related to the prognosis of HCC in TCGA database. Prognostic significance of ABCC1, ABCC4, ABCC5 and ABCC6 was also observed in the Guangxi cohort. In the Guangxi cohort, both PCR (polymerase chain reaction) and IHC (immunohistochemical) assays demonstrated higher expression of ABCC1, ABCC4, ABCC5 in HCC compared to liver tissues, while the opposite was true for ABCC6. GSEA analysis indicated that ABCC1 was associated with tumor differentiation, nod like receptor signal pathway, etc. It also revealed that ABCC4 might play a role in HCC by regulating epithelial-mesenchymal transition, cytidine analog pathway, met pathway, etc. ABCC5 might be associated with fatty acid metabolism and KRT19 in HCC. ABCC6 might impact cell cycle in HCC by regulating E2F1 and myc. The relationship between ABCC genes and immune infiltration was explored and ABCC1,4,5 were found to be positively associated with infiltration of multiple immune cells, while ABCC6 was found to be the opposite In conclusion, ABCC1, ABCC4, ABCC5 and ABCC6 might be prognostic biomarkers in HCC. The prognostic models constructed with ABCC1, ABCC4, ABCC5 and ABCC6 had satisfactory efficacy.